Strategic Net Assessment: Opportunities and Pitfalls. Issue 6 (2nd November 2018) - Roberts, Peter; Kaushal, Sidharth
Abstract : The recent interest in a net assessment capability by the UK Ministry of Defence raises questions regarding the usefulness of this instrument. While some might argue that the eclectic nature of net assessment breaks the moribund and short-term thinking that can all too often blinker policy, others contend that it is little more than shorthand for unstructured, unsubstantiated and often Delphic pronouncements. In this article, Peter Roberts and Sidharth Kaushal argue that the key to leveraging the strengths of net assessment is understanding the nature of the tool and the ways in which flexibility can be married with rigour to glean insights from this method while minimising its pitfalls.